Virtual technologies used for the construction of teaching and learning in the health area (Research, Society and Development, 2020)
Technology is the set of scientific knowledge and principles that apply to the planning, construction and use of equipment that allows user interaction with an educational program contributing to learning. The objective of the present study is to approach through a literature review the current aspects of the use of virtual technologies in the construction of teaching and learning in the health area. The computer is a tool that promotes interaction, provides students with moments of concentration on a task, and because they are fully involved, students take pleasure in what they are doing and develop the educational process for learning. The growing use of technology is allowing the population to access services and data, regardless of their physical location. Teaching-learning is always in development, especially with changes in globalization, through the creation of new technological inventions that contribute to learning in dental practice. Education is linked to technology, with knowledge and handling of technological resources of fundamental importance for the process of knowledge development, teaching and learning.